Mitigating perioperative pressure injuries in microsurgical breast reconstruction - Fazzalari, Amanda; Gebhardt, Susanna; Hamaguchi, Ryoko; Agarwal, Shailesh (Frontiers in Surgery, 2025)
Pressure injuries (PI) that develop in the operating room (OR) account for just under half of all hospital acquired pressure injuries (HAPI) and contribute significantly to the high cost and patient morbidity of HAPI. Microvascular autologous breast reconstruction poses specific risks to PI development in patients and should be addressed by the reconstructive microsurgeon. Standard risk factors for perioperative PI include patient immobility, absent pain perception, and challenges to maintaining normal body temperature while under general anesthesia for surgery. Specific intraoperative risk factors relevant to patients undergoing microvascular autologous breast reconstruction include extended length of surgery and patient repositioning. The risk of PI increases significantly when operative time exceeds 3 h and patient repositioning, with changes in positioning subjecting specific anatomic locations to increased pressure and friction. For these reasons, placement of positioning devices at high-risk anatomical locations is particularly important, such as the use of polyurethane or polyether mattresses, multilayered silicone foam dressings, and gel, foam, or fluidized positioners. The implementation of periodic body positioning checks and clear communication between surgical teams regarding awareness and status of pressure points is helpful in mitigating risk of perioperative PI. Preoperative risk assessments and skin exams may also be useful, as well as postoperative skin exams and early movement out of bed on postoperative day 0 and ambulation on postoperative day 1. These guidelines will reduce the risk of PI development in patients undergoing reconstructive breast surgery.